Fulminant Perianal Donovanosis Manifesting as Septic Shock in a Treatment-Naïve AIDS Patient: A Clinico-Pathological Case Report - Rahmat Firdaus Dwi Utama; Muhammad Eko Irawanto; Ayu Kusuma Dewi; Shelly Lavenia Sambodo; Stella Gracia Octarica; Sugih Primas Adjie (HM Publisher, 2025)
Donovanosis (Granuloma Inguinale), caused by Klebsiella granulomatis, is a rare sexually transmitted infection that can follow a devastating course in severely immunocompromised individuals. Its clinical progression in the context of advanced acquired immunodeficiency syndrome (AIDS) is not extensively documented. We present a case of fulminant donovanosis to illustrate its potential for rapid systemic deterioration and mortality. A 20-year-old Indonesian man, with a recent diagnosis of human immunodeficiency virus (HIV) for which he was treatment-naïve, presented with a two-month history of extensive, painful perianal ulcerations. Clinical examination revealed large, coalescing,